2011
DOI: 10.4067/s0718-16202011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Lotus corniculatus cultivars using transferable microsatellite markers

Abstract: D. Alem, R. Narancio, P. Díaz Dellavalle, M. Rebuffo, R. Zarza, and M. Dalla Rizza. 2011. Molecular characterization of cultivars of Lotus corniculatus using transferable microsatellite markers. Cien. Inv. Agr. 38(3): 453-461. Lotus corniculatus L. is the most important agricultural species in the genus Lotus and is the most widely distributed Lotus species worldwide. L. corniculatus genotypes form complex groups that are difficult to recognize both morphologically and biochemically. Given the extensive and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…from the Old and New Worlds (Allan and Porter, 2000). Furthermore, high allelic variability was confirmed within and among L. corniculatus cultivars and L. japonicus accessions (Jiang and Gresshoff, 1997;Kawaguchi et al, 2001;Alem et al, 2011). ISSR and nrITS markers used to study genetic variability between L. corniculatus, L. stepposus, and L. ucrainicus revealed that L. ucrainicus is a hybrid between L. corniculatus and L. stepposus (Kramina et al, 2012;Kramina, 2013).…”
mentioning
confidence: 94%
“…from the Old and New Worlds (Allan and Porter, 2000). Furthermore, high allelic variability was confirmed within and among L. corniculatus cultivars and L. japonicus accessions (Jiang and Gresshoff, 1997;Kawaguchi et al, 2001;Alem et al, 2011). ISSR and nrITS markers used to study genetic variability between L. corniculatus, L. stepposus, and L. ucrainicus revealed that L. ucrainicus is a hybrid between L. corniculatus and L. stepposus (Kramina et al, 2012;Kramina, 2013).…”
mentioning
confidence: 94%